Metal Toxicity Links to Alzheimer's Disease and Neuroinflammation. Issue 9 (19th April 2019) - Huat, Tee Jong; Camats-Perna, Judith; Newcombe, Estella A.; Valmas, Nicholas; Kitazawa, Masashi; Medeiros, Rodrigo
Abstract: As the median age of the population increases, the number of individuals with Alzheimer's disease (AD) and the associated socio-economic burden are predicted to worsen. While aging and inherent genetic predisposition play major roles in the onset of AD, lifestyle, physical fitness, medical condition, and social environment have emerged as relevant disease modifiers. These environmental risk factors can play a key role in accelerating or decelerating disease onset and progression. Among known environmental risk factors, chronic exposure to various metals has become more common among the public as the aggressive pace of anthropogenic activities releases excess amount of metals into the environment. As a result, we are exposed not only to essential metals, such as iron, copper, zinc and manganese, but also to toxic metals including lead, aluminum, and cadmium, which perturb metal homeostasis at the cellular and organismal levels. Herein, we review how these metals affect brain physiology and immunity, as well as their roles in the accumulation of toxic AD proteinaceous species (i.e., β-amyloid and tau). We also discuss studies that validate the disruption of immune-related pathways as an important mechanism of toxicity by which metals can contribute to AD. Our goal is to increase the awareness of metals as players in the onset and progression of AD. Graphical abstract: Unlabelled Image Highlights: Genetics, brain immunity and environment play a role in AD. Anthropogenic activities are increasing human exposure to environmental metals. Dyshomeostasis of metals drives inflammation, β-amyloid, tau and neurodegeneration. Metal chelation is a promising strategy for the management of AD. Better understanding of metals in the brain may help in the treatment of AD.